Udviklingen af rumopfattelsen 1600-2000, filosofihistoriske hovedtræk - Brock, Steen (Slagmark - Tidsskrift for idéhistorie, 2018)
The paper tries to give a survey of the historical development of physical and philosophical ideas of space after Descartes and Newton. A special focal point is Kant´s idea of a schematism and three kinds of afterglows of this idea; the notion of a work of art, the notion of scientific model, and finally the unity of action and space in phenomenology. The paper suggests that works within the recent spatial turn perhaps have failed to rethink the unity between material, social, and personal relations, and that an assessment of the later Wittgenstein´s micro-phenomenology could pave the way for a stronger “second spatial turn”.